The role of microfinance in women's empowerment : a comparative study of rural & urban groups in India - Ajwani-Ramchandani, Raji (Emerald Publishing Limited, 2017)
While the important topic of women's empowerment through microfinance has been the subject of academic and practitioner interest, Ramchandani examines these issues from brand-new perspectives. This new work focuses on the Self-Help Group (SHG) model, an under-studied aspect of microfinance practice, and looks at both rural communicates and urban slums. Ramchandani presents recent empirical work from India including first-hand field-level case studies, where microfinance plays a key development role in reducing poverty, addressing women's empowerment, and fostering rural economic growth.- Resumé vydavatel
Obsahuje index.
Keywords: mezinárodní hospodářské vztahy; mikrofinance -- Indie; international economic relations; microfinance -- India; případové studie; srovnávací studie; elektronické knihy; case studies; comparative studies; electronic books